Figure 5 from Exploiting Natural Killer Cell Engagers to Control Pediatric B-cell Precursor Acute Lymphoblastic Leukemia - Natalia Colomar-Carando (14611340) (2025)
NKCEs override HLA-I inhibitory interactions. Degranulation activity of NK cells (All NK, gating on CD3−CD56+) and different NK-cell subsets [single (s)KIR2DL1+, KIR2DL3+/KIR3DL1+, and KIR−NKG2A+, identified by appropriate gating strategy reported in Supplementary Fig. S1] from healthy donors (n = 3) or transplanted patient (n = 1) upon 4-hour coculture with MHH-CALL-4 cells in presence of IC-NKp46- or CD19-NKp46-NKCE at 100 μg/mL. Results from three independent experiments are reported. A, Contour plot of a representative donor showing the degranulation of different NK-cell subsets in the presence of the target cells and NKCEs. Numbers indicate the percentage of cells in each quadrant. B, Data from 3 healthy donors are reported. C and D, Degranulation of NK-cell subsets from 1 patient 1-year after haplo-HSCT. C, Contour plot of flow cytometry (raw data). D, Graphical representation.